THE IMPLEMENTATION OF MIND MAPPING IN TEACHING WRITING NARRATIVE TEXT FOR TENTH GRADES OF SMAN 18 SURABAYA (RETAIN, 2013)
Writing is one of the language skills that has to be mastered by the students as well as the three other skills. Writing is considered the most difficult one because when doing writing activity, the students are required to pay attention to the content, organization, vocabulary, language use and mechanics simultaneously. The students also should arrange and organize the ideas clearly so that the readers do not misunderstand on what they write. The students also sometimes get difficulties in getting ideas to write. Because of many things that the students have to think to make a good writing, the students often get difficulties in expressing their ideas into a well composition. The mind mapping is effective strategy that can help the students in creating well composition because they are allowed to discuss their composition with their partners. Mind mapping also allowed the students to get and improves by observing the story given by teacher. For the reason, the researcher is interested to exploring the implementation of writing narrative texts by using mind mapping to the tenth graders and find out how are the students’ compositions after using mind mapping method. Writing activity needs long process that consists of pre – writing, drafting, revising, editing and publishing. The implementation of writing narrative texts by using mind mapping follows the steps of the writing process. Think pair share technique itself has three stages that are think , pair and share. So, in the implementation, the students do revising and editing activities in the “think” stage. While, the students do revising and editing activities in the “pair” stage. At the last, they can publish their composition in “share” stage. One of text types that can be taught by using mind mapping is narrative text. It is one of the texts which is taught to tenth graders of Senior High School. The researcher used descriptive qualitative researcher in conducting her study. The subjects of the study were the teacher and tenth graders of SMAN 18 Surabaya. The class observed was X – 5. The researcher instruments that were used by the researcher to collect the data were observation checklist, observation field note, and the students’ task. Those instruments were used to describe the way how the teacher implemented the mind mappingin teaching narrative texts and the students’ writing composition. From the data that was collected during observations, is revealed that the implementation of mind mapping was conducted twice in three meeting. The implementation was successfully and also can help the students to improve their writing skills. Is proven from the students’ writing progress in terms of each component in composition. The researcher concluded that the implementation mind mapping was effective to be used in teaching narrative texts; especially to the tenth graders of SMAN 18 Surabaya because the implementation of the technique and method could run well and could help the students create well composition. Moreover, the researcher expects for further researcher to conduct a similar research about the implementation of mind mapping in different skills. Key words : teaching writing, narrative text, the mind mapping.